Biological Invasions in South Africa 2020
DOI: 10.1007/978-3-030-32394-3_27
|View full text |Cite
|
Sign up to set email alerts
|

South Africa as a Donor of Alien Animals

Abstract: This review provides the first assessment of animal species that are native to South Africa and invasive elsewhere in the world. While around a twelfth of all naturalised plants in the world are native to South Africa, there are very few examples of South African native marine, terrestrial, or freshwater animals becoming invasive elsewhere. We provide a narrative of each of the 34 cases that we could find. Three of these species, the Common Waxbill, Estrilda astrild, the Mozambique Tilapia, Oreochromis mossamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 188 publications
(235 reference statements)
0
8
0
Order By: Relevance
“…The species has successfully established invasive populations in Mauritius, Réunion, and near Cape Town (Constantia, South Africa) (Measey et al 2017;Telford et al 2019;Measey et al 2020b). Recent genetic analyses have confirmed that all three invasive populations originated from a clade located in the area around the port city of Durban in eastern South Africa (Telford et al 2019).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The species has successfully established invasive populations in Mauritius, Réunion, and near Cape Town (Constantia, South Africa) (Measey et al 2017;Telford et al 2019;Measey et al 2020b). Recent genetic analyses have confirmed that all three invasive populations originated from a clade located in the area around the port city of Durban in eastern South Africa (Telford et al 2019).…”
Section: Study Speciesmentioning
confidence: 99%
“…The decoupling of traits might also be a potential driver for the apparent similarities in growth rates of guttural toad tadpoles. Furthermore, the guttural toad is an infamous urban exploiter with synanthropic behaviour, frequently making use of artificial light sources for foraging and artificial bodies of water for hydration and reproduction (du Preez et al 2004;Measey et al 2017;Vimercati et al 2017;Baxter-Gilbert et al 2020;Measey et al 2020b). Thus, the terrestrial stage of the species might benefit from ecological opportunities in urban environments that are not available for the aquatic stage and growth rate might be decoupled between the tadpole and adult stage.…”
Section: Modelmentioning
confidence: 99%
“…Guttural toads have a wide native distribution across large sections of east and southern Africa, excluding arid regions in Botswana, Namibia and western South Africa, and with invasive populations in Mauritius, Réunion and near Cape Town in South Africa (Measey et al., 2017; Measey et al., 2020; Telford et al., 2019; Figure 1). Recently, molecular studies have shown that all three invasive populations originated near the port city of Durban, within the species native range in South Africa (Telford et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The long‐standing persistence of guttural toads ( Sclerophrys gutturalis ) in Mauritius represents one such understudied invasive population with an identified need for ecological studies to be undertaken (Kumschick et al., 2017; Measey et al., 2020). Guttural toads were introduced to Mauritius as biocontrol agents for insect pests in 1922 and became invasive shortly thereafter (Cheke, 2010; Cheke & Hume, 2008; Owadally & Lambert, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation